The Judge in an Evolving Society - Cooke, Robin (Victoria University of Wellington Law Review, 1998)
In this address, given to Judges and Judicial Officers of the High Court of Hong Kong on 17 December 1997, Lord Cooke speaks of the development of a common law of the world with particular reference to the Basic Law of Hong Kong.